The Book of the Cat - Bonsall, Elizabeth Fearne, 1861-1956; Humphrey, Mabel (Salt Lake City, UT : Project Gutenberg, 2007)
"The Book of the Cat" by Elizabeth Fearne Bonsall and Mabel Humphrey is a collection of illustrated stories and verses centered around the lives and antics of cats, likely written in the early 20th century. The book explores themes of friendship, adventure, and the whimsical lives of various cats. It is presented in a playful tone, appealing to both children and cat enthusiasts alike. The narrative features a variety of feline characters, including Ebony, a brave black cat, and Snowball, a pampered white Angora cat, whose friendship reveals their contrasting personalities. Other tales within the book depict the misadventures of kittens, their playful behaviors, and their encounters with the world around them, highlighting their innocence and curiosity. Each story is accompanied by charming illustrations, enhancing the whimsical feel of the collection. Themes of adventure, companionship, and the quirks of cat behavior permeate the stories, making it an endearing and entertaining read for animal lovers. (This is an automatically generated summary.)
Release date is 2007-07-10
E-text prepared by Jason Isbell, Katie, Christine D., and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Rare Book and Special Collections Division of the Library of Congress (http://www.loc.gov/rr/rarebook/digitalcoll/digitalcoll-children.html)
Keywords: Cats -- Juvenile fiction